Analysis of the Relationship Between Trade Openness and Technology Innovation in Enhancing Economic Growth in Multinational Companies - Elli Sulistyaningsih; Sugeng Siswanto (International Journal of Sustainable Applied Sciences, 2023)
Since entering the Millennium era, world developments in the field of technology have been running at high acceleration. Several countries that were once well aligned in the economic and industrial fields are now lagging behind other countries. Rapid progress is due to very good mastery of technology so that it is able to compete globally. Mastering technology is an integral part of qualified human resource capabilities which are strongly influenced by education and economic capacity as a support. To support the necessary attractiveness support and internalization of work attitudes in encouraging the nation's competitiveness. Technological innovation plays a very important role in capturing trade for economic growth in multinational companies. Technological innovation can improve operational efficiency, improve product and service quality, encourage new product and service innovations, and facilitate access to global markets. Therefore, it is important for multinational companies to continue to invest in technological innovation in order to maintain their competitiveness in the global market.